Effect of resistive heating on the bond properties between iron-based shape memory bars and cement mortar. (1st May 2023) - Liu, Ziqing; Dong, Zhiqiang; Sun, Yu; Zhu, Hong; Wu, Gang; Sun, Changjun; Soh, Chee-Kiong
Abstract: Iron-based shape memory alloys (Fe-SMAs) have been widely studied as a new type of prestressing material for near-surface mounted (NSM) or external strengthening, and have been used in numerous strengthening projects in Europe. However, Fe-SMAs have not been widely used in new structures due to their uncertain bond properties after high-temperature activation. Therefore, a new type of application in new structures is proposed, which is composed of Fe-SMA bars, plastic corrugated pipes and high-temperature-resistant cement mortar. The bond properties between Fe-SMA bars and cement mortar after resistive heating were investigated through pull-out tests. The influence of different heating temperatures and heating times on the bond properties was analyzed. It was shown that when the temperature of the inner Fe-SMA bars was 150 °C–350 °C, the surface temperature of the plastic corrugated pipes was only 35 °C–65 °C, which indicated that the activation process would not transfer excessive heat to the concrete outside the plastic corrugated pipes. With the increase of the heating temperature, the ultimate bond strength, bond stiffness, residual bond stress, and energy dissipation all gradually decreased. Compared with the specimens at ambient temperature, the specimens could still maintain a high ultimate bond strength with only approximately 10% loss after being heated to 200 °C and cooled down. When the activation temperature was below 300 °C, the more serious bond degradation could be observed with the longer heating time. However, when the temperature exceeded 300 °C, the influence of heating time was negligible. In addition, prediction models for the ultimate bond strength and the bond-slip curves were proposed, which could provide references for subsequent studies. Highlights: The bond properties between Fe-SMA bars and mortar after resistance heating were investigated. The PZT was used to monitor the interface damage after high-temperature and the pull-out test. The specimens after 200 °C could still maintain a high ultimate bond strength retention of 90%. The prediction models for the ultimate bond strength and the bond-slip curves were proposed.